High Efficacy of Therapeutic Equine Hyperimmune Antibodies Against SARS-CoV-2 Variants of Concern - Moreira-Soto, Andres; Arguedas, Mauricio; Brenes, Hebleen; Buján, Willem; Corrales-Aguilar, Eugenia; Díaz, Cecilia; Echeverri, Ann; Flores-Díaz, Marietta; Gómez, Aarón; Hernández, Andrés; Herrera, María; León, Guillermo; et al. (Frontiers in Medicine, 2021)
SARS-CoV-2 variants of concern show reduced neutralization by vaccine-induced and therapeutic monoclonal antibodies; therefore, treatment alternatives are needed. We tested therapeutic equine polyclonal antibodies (pAbs) that are being assessed in clinical trials in Costa Rica against five globally circulating variants of concern: alpha, beta, epsilon, gamma and delta, using a plaque reduction neutralization assay. We show that equine pAbs efficiently neutralize the variants of concern, with inhibitory concentrations in the range 0.146-1.078 µg/mL, which are extremely low concentrations when compared to pAbs doses used in clinical trials. Equine pAbs are an effective, broad coverage, low-cost and a scalable COVID-19 treatment.